Biopsy Diagnosis of Peripheral Neuropathy - Bilbao, Juan M.; Schmidt, Robert E. (Springer International Publishing : Imprint: Springer, 2015)
Peripheral nerve analysis is a challenging task for pathologists, given the advent of new diagnoses and techniques of analysis and the impact of molecular genetics. This book presents a simple, logical method for constructing a differential diagnosis based on pathology and clinical presentation. It also provides advice on the selection of ancillary molecular, immunohistochemical and genetic techniques to establish a definitive diagnosis. Clear, authoritative guidance is offered on diagnosis of the full range of neuropathies with the aid of a wealth of high-quality color photomicrographs and electron micrographs. The pathologist will benefit greatly from the identification of a variety of artifacts and normal structures occasionally encountered in nerve biopsies that need to be distinguished from specific pathologic alterations. This user-friendly, practical text will be an invaluable aid in achieving the most specific diagnosis possible.